STRATEGI GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM PEMBENTUKAN AKHLAKUL KARIMAH SISWA (STUDI MULTI SITUS DI SD MUHAMMADIYAH 24 KETINTANG SURABAYA DAN SDIT GHILMANI KETINTANG BARAT SURABAYA)”. - m.zaini, thohaputra (POJOK GURU: Jurnal Keguruan dan Ilmu Pendidikan, 2024)
AbstractIn this research the author used a qualitative approach with a multisite research type. Data collection techniques used include: 1) Participant Observation, 2) Interviews or In-depth Interviews, 3) Documentation. Data collected through these three techniques were analyzed from single sites and cross-site analysis. The results of this research show that: 1) The Islamic Religious Education (PAI) Teacher Program in the formation of students' akhlakul karimah at SD Muhammadiyah 24 Ketintang Surabaya and SDIT Ghilmani Ketintang Barat Surabaya is a) implementing its vision and mission, b) attending the beginning of the year meeting and preparing strategic plan. c) Preparation of an Islamic Religious Practice Activity Book. d) Involving all stakeholders in planning activities for the formation of students' morals and this is done by: a) Habituation carried out at SDIT Ghilmani Ketintang Barat Surabaya in the formation of morals, namely wearing uniforms that cover the private parts, for both men and women. b) Get into the habit of shaking hands with teachers, c) Bring in teachers to read and write the Qur'an from the nearest Islamic boarding school and include these lessons in 2-3 hours of learning. d) provide a good example for students, for example, before students do it, the teacher does it first, before students are told to maintain cleanliness, the teacher first does it. 3) Evaluation of Islamic Religious Education (PAI) teachers in the formation of students' morals at SD Muhammadiyah 24 Ketintang Surabaya and SDIT Ghilmani Ketintang Barat Surabaya: a) teachers always evaluate the Islamic Religious Education (PAI) teacher program in the formation of students' morals that has been implemented supported by the school principal, b) collaboration between the principal and Islamic Religious Education (PAI) teachers to carry out continuous evaluation of the programs implemented, c) Weekly evaluations are carried out by correcting the religious assignments that have been given to students. d) Semester evaluations are held every semester exam to evaluate the activities of Islamic Religious Education (PAI) teachers in the formation of students' morals carried out by students in that semester. e) Evaluation of the formation of students' morals is also carried out annually, namely that there are special requirements for children who will move up to a higher class, for example to go up to class IV and V children must memorize Asma' al-Husna, 10 types of important prayers and 15 short suras. Religious bills as an annual evaluation are one of the requirements for students' grade promotion. Keywords : Islamic Education Teacher Strategy, Formation of Karimah's morals